The Effect of Brand Awareness and Perceived Quality Through Purchas Intention on Purchase Decision on Transit Advertising Commuter Lines in Jabodetabek (An Empirical Study of Le Minerale Products) - Amanda Valentine; Supriadi Thalib; Harimurti Wulandjani; Nurul Hilmiyah (Greenation International Journal of Tourism and Management, 2026)
This study aims to examine the influence of Brand Awareness and Perceived Quality on Purchase Decision through Purchase Intention in transit advertising on the Jabodetabek Commuter Line, with an empirical study of Le Minerale products. The sampling technique employed was non-probability sampling using a purposive sampling approach. Data were collected through the distribution of questionnaires to 200 respondents. This study applied Partial Least Squares–Structural Equation Modeling (PLS-SEM) as the data analysis technique, utilizing SmartPLS software version 4.0.9.9.The findings indicate that Brand Awareness and Perceived Quality have a positive and significant effect on Purchase Intention and Purchase Decision. Furthermore, Purchase Intention, as an intervening variable, plays a positive and significant role in mediating the relationship between Brand Awareness and Perceived Quality and Purchase Decision.